Propuesta didáctica para el fortalecimiento en la enseñanza y el aprendizaje de la comprensión lectora en estudiantes de quinto grado (2019)
The study presented was intended to design a didactic proposal to strengthen reading comprehension processes from teaching and learning in fifth grade students of IE San José de Luruaco, taking into account the relevance of text comprehension in the educational processes. The work followed the theoretical foundations of Solé (1987-1992), Teberosky (1998), Rosenblat (1978), Rumerlhar (1980), Rosenblatt (2013), Abreu (2015), Goldman (1996), the Ministry of National Education (MEN, 2017), along with others. The research is part of the Socio-Critical paradigm, with a mixed approach considering the use of quantitative and qualitative instruments, for the search for answers from the 27 teachers and 32 students of the IE San José de Luruaco EI. Transmission and repetition were highlighted as an educational activity, with evaluation strategies oriented to cognitive conflict, group organization of students and mediated participation strategies, highlighting the pedagogical reflective practice from a constructivist approach. According to the level of reading comprehension, the greatest degree of difficulty lies in the level of critical type. It is concluded that the processes of reading comprehension are indispensable for the academic development of the students, but that they need to be well managed conceptually and methodologically by the teachers.